(1)H, (13)C, and (15)N NMR assignments of the Pyrococcus abyssi DNA polymerase II intein - Liu, Jiajing (2011)
Protein splicing is a precise post-translational process mediated by inteins. Inteins are intervening proteins that cleave themselves from a precursor protein while joining the flanking sequences. Here we report the (15)N, (13)C, and (1)H chemical shift assignments of the intein from DNA polymerase II of Pyrococcus abyssi (Pab PolII intein), which has been recombinantly overexpressed and isotopically labeled. The NMR assignments of Pab PolII intein are essential for solution structure determination and protein dynamics study.